Multifunctional Artefacts and Collocation. (12th December 2022) - Ruben, David-Hillel
There appear to be multifunctional artefacts of a type such that none of their functions can be attributed only to some proper part of the artefact. I use two examples of allegedly multifunctional artefacts of this kind in what follows, one due to Lynne Rudder Baker (aspirin) and another of my own (a spork). The two examples are meant to make the same point. I discuss her aspirin example, since its discussion has entered the literature, but without its being dealt with satisfactorily. My example is, I believe, more intuitive than that of aspirin, which Baker introduced in her response to a challenge to her views, and so I will mostly rely on my example of a spork, especially at the end of the paper, to make my case. I argue that in at least those two cases, if the standard arguments for distinguishing between an object and what constitutes it are sound, an argument showing that what we might have taken to be a single multifunctional object is in fact a case of multiple single-function artefacts which collocate. Or almost. There is one further assumption needed for these cases, beyond what the constitution cases require, and I produce reasons for accepting that assumption.